Hubungan Kualitas Tidur Dengan Konsentrasi Belajar Anak di SMP N 18 Kota Bengkulu Tahun 2025 - Reni Parida; Yatri Hilinti; Berlian Kando Sianipar (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Sleep quality is a basic need that greatly affects children's cognitive functions, especially their concentration in learning. Sleep disturbances can cause fatigue, decreased attention, and difficulty in focusing during the learning process. This study aims to determine the relationship between sleep quality and children's concentration in learning at SMP Negeri 18 Kota Bengkulu in 2025. This study used a correlational analytical design with a cross-sectional approach. The population in this study consisted of all 314 ninth-grade students at SMP Negeri 18 Kota Bengkulu, with a sample size of 76 respondents selected using the Slovin formula and proportional stratified random sampling technique. The research instruments used the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality and a learning concentration questionnaire. Data analysis was performed univariately and bivariately using the chi-square test with a significance level of α = 0.05. The results of the univariate test analysis showed that most respondents had poor sleep quality (60 or 78.9%), and a small number of respondents had poor learning concentration (18 or 23.7%). The results of the bivariate analysis show a significant relationship between sleep quality and learning concentration among students at SMP Negeri 18 Kota Bengkulu with a P value of 0.012. The results of this study indicate that there is a significant relationship between sleep quality and learning concentration among children. Therefore, it is hoped that the school can provide education on the importance of quality sleep, and students are expected to be able to apply healthy sleeping habits to support concentration and optimal learning processes.